Technology Information Management Applied To Rail Transportation System - Daniel Dăneci-Pătrău (Ovidius University Annals: Economic Sciences Series, 2020)
Throughout its evolution the railway transport system has become a complex specialized system, with remarkable characteristics and under conditions of economic efficiency superior to the other means of transportation. By connecting all counties through a sole network, rail transport plays an important role in the economic, political and strategic life of the country. This role is emphasized by the fact that on its optimal running depend the economic agents’ supply with raw necessities and materials, the population’s rapid supply with consumer goods, the ensuring of passenger transportation. Any delay or disturbance in the railway traffic yields deep repercussions on the entire social life flow. This article has been given over to the conclusions held by the research on the information regarding the main activities and resources of the Romanian rail transport system.